1999
DOI: 10.1007/bf02467610
|View full text |Cite
|
Sign up to set email alerts
|

Separation of nucleoside mono-, di- and triphosphates by capillary electrophoresis via cadmium complexation

Abstract: SummaryThe CE separation of twelve nucleotides (5'-mono-, di-, triphosphates of adenosine, guanosine, cytidine and uridine) was improved by adding cadmium ion to the ammonium citrate/citric acid buffer (pH 5, ionic strength 100 mM). Cadmium ion acts as a complexing agent for some nucleotides (ATP, CTP, GTP, UTP, GDP). In order to accelerate the separation, the electroosmotic flow was reversed by flushing the fused-silica capillary with 0.2 % aqueous solution of the polycationic surfactant hexadimethrine bromid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…Cahours et al [6][7][8] reported the addition of inorganic cations to the buffer could improve the resolution of nucleotide mono-, di-and triphosphates in CZE separation [6][7][8]. In this work, either magnesium chloride or zinc acetate was tested to see whether the resolution of UMP isomer would be improved.…”
Section: Interaction Of Nucleotides With Metal Ionsmentioning
confidence: 96%
See 1 more Smart Citation
“…Cahours et al [6][7][8] reported the addition of inorganic cations to the buffer could improve the resolution of nucleotide mono-, di-and triphosphates in CZE separation [6][7][8]. In this work, either magnesium chloride or zinc acetate was tested to see whether the resolution of UMP isomer would be improved.…”
Section: Interaction Of Nucleotides With Metal Ionsmentioning
confidence: 96%
“…The method appears to be very effective to resolve all 12 nucleotide isomers in less than 15 min. Cahours et al [6][7][8] have studied the complexation equilibrium between nucleotides and inorganic cations (Mg 21 , Ca 21 , Cd 21 , and Zn 21 ) by CE. These studies would be useful for optimization of the separation of nucleoside mono-, di-and triphosphates by CE according to their different affinity for inorganic cations added to the buffer.…”
Section: Introductionmentioning
confidence: 99%
“…CE has been proven to have several advantages over HPLC, particularly in terms of its high efficiency and small volume requirements. Here, we only studied those for the separation of nucleoside monophosphates [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Among them, a number of studies involved the addition of quaternary ammonium salt as EOF modifier [12,25,27,29,30], cyclodextrin [15,23], acetonitrile [20,22], mixture of cyclodextrin and MgCl 2 [23], or metal ions [23,25,27,30] in the background electrolyte (BGE).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we only studied those for the separation of nucleoside monophosphates [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Among them, a number of studies involved the addition of quaternary ammonium salt as EOF modifier [12,25,27,29,30], cyclodextrin [15,23], acetonitrile [20,22], mixture of cyclodextrin and MgCl 2 [23], or metal ions [23,25,27,30] in the background electrolyte (BGE). Examples also included micellar electrokinetic chromatography (MEKC) [23,24], the use of cross-linked polyacrylamide [13], polyethylene oxide [26], diol-bonded [28], and Ucon-coated columns [14,16,18,22], or medium at pH above 10 [19,21,31] to achieve a better separation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, CE is a rapid and convenient technique for studying the complexation (stoichiometry and stability constants) of nucleotides with inorganic ions versus pH [8]. Recently, we achieved [9] the separation of nucleoside mono-, di-and triphosphates (5'-isomer) in about five minutes by adding cadmium ion to an ammonium citrate/citric acid buffer. The concentration of this complexing agent modified the electrophoretic mobilities of nucleoside mono-, di-, triphosphates differently, depending on the nature of the base and the number of phosphate groups.…”
Section: Introductionmentioning
confidence: 99%